PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ARTICULATE STORYLINE 3 PADA MATERI MANFAAT KEBERAGAMAN DAN MELESTARIKAN KEBERAGAMAN BUDAYA - Ridha Maulidah; Wawan Syahiril Anwar; Nur Hikmah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Ridha Maulidah. 037121090. Development of Articulate Storyline 3-BasedLearning Media on the Benefits of Diversity and Preserving Cultural Diversity. Thisresearch aims to develop learning media based on Articulate Storyline 3 on thematerial Benefits and Preservation of Cultural Diversity, with an Research andDevelopment (R&D) method using the ADDIE (Analysis, Design, Development,Implementation, and Evaluation) model. The research was conducted at SDNBaranangsiang grade IV with 1 teacher and 18 students as respondents. Thevalidation results showed that the developed media was very feasible, with anassessment of 97% media experts, 91% linguists, 84% lecturer material experts,95% teacher material experts, 98% teacher responses, and 95% studentresponses. This learning media is very suitable to be used as a tool in the learningprocess.